2019
DOI: 10.1101/519793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired Regulation of Redox Transcriptome during the Differentiation of iPSCs into Induced Cardiomyocytes (iCMs)

Abstract: Background: Reprogramming of somatic cells into pluripotent stem cells (iPSC) and subsequent differentiation into iPSC-derived cardiomyocytes (iCM) seems to be a promising strategy for cardiac regenerative therapy. However, recent failure or poor outcomes in cardiac cell therapy warrants further investigation focusing on the infarction/wound environment (site of healing) to improve the cardiac regenerative medicine. Here, using next generation sequencing (NGS), we analyzed the global transcriptome to discover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…19 It is reported that RPS27A play a role in the regulation of cell cycle and promote cell proliferation. 20 This was consistent with the result of the present study that shows the expression Furthermore, KEGG pathway enrichment analysis showed that the five modules were mainly enriched in cell cycle, DNA replication, nucleotide excision repair, ribosome, ribosome biogenesis in eukaryotes, ErbB signaling pathway, EGFR tyrosine kinase inhibitor resistance, pancreatic cancer, breast cancer, prostate cancer, microRNAs in cancer, proteoglycans in cancer, pathways in cancer, endocytosis. Interestingly, it is notable that both DNA replication pathway and nucleotide excision repair pathway appeared twice in the KEGG pathway analysis of the five modules, accounting for 12 and 4 genes, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…19 It is reported that RPS27A play a role in the regulation of cell cycle and promote cell proliferation. 20 This was consistent with the result of the present study that shows the expression Furthermore, KEGG pathway enrichment analysis showed that the five modules were mainly enriched in cell cycle, DNA replication, nucleotide excision repair, ribosome, ribosome biogenesis in eukaryotes, ErbB signaling pathway, EGFR tyrosine kinase inhibitor resistance, pancreatic cancer, breast cancer, prostate cancer, microRNAs in cancer, proteoglycans in cancer, pathways in cancer, endocytosis. Interestingly, it is notable that both DNA replication pathway and nucleotide excision repair pathway appeared twice in the KEGG pathway analysis of the five modules, accounting for 12 and 4 genes, respectively.…”
Section: Discussionsupporting
confidence: 92%